2017
DOI: 10.4103/aer.aer_51_17
|View full text |Cite
|
Sign up to set email alerts
|

Fears and perceptions associated with regional anesthesia: A study from a tertiary care hospital in South India

Abstract: Aims:To assess the patients’ fears and their perception about regional anesthesia and to study the correlation between fears and perception and demographic profile.Design:A prospective cross-sectional survey on 150 patients scheduled for surgery under regional anesthesia (RA).Materials and Methods:The structured questionnaires composed of patients’ demographic data and questions regarding patients’ fears about RA. Questionnaires along with consent forms were sequentially distributed to patients. American Socie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…In many studies, the rates of patient satisfaction with spinal anesthesia are reported to be high. In the same studies, the reasons behind patient dissatisfaction are listed as the excessively invasive nature of the intervention, lithotomy, being awake, and the discomfort caused by the operating room conditions (Bheemanna et al, ; Choi, In, & Shin, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many studies, the rates of patient satisfaction with spinal anesthesia are reported to be high. In the same studies, the reasons behind patient dissatisfaction are listed as the excessively invasive nature of the intervention, lithotomy, being awake, and the discomfort caused by the operating room conditions (Bheemanna et al, ; Choi, In, & Shin, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the conscious state of patients undergoing spinal anesthesia may increase their level of anxiety, making them feel even more vulnerable and fragile (Karlsson, Ekebergh, Mauléon, & Almerud Österberg, ; Kent et al, ). Such anxiety may be further intensified due to the application of an intravenous cannula, anesthetic injection into the spine, being able to witness the operation, and feeling pain (Bheemanna, Channaiah, Gowda, Shanmugham, & Chanappa, ). The operating room environment also causes fear and anxiety in patients (Dolgun & Candan Dönmez, ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also difficult for them to differentiate the risk and benefits of anesthesia type. [11][12][13][14] Different factors influence the attitude of parturients towards anesthesia techniques for cesarean section. Nausea and vomiting (27%), fear of pain(34%), and fear of needle puncture (15%) were the most important predictors of attitude of parturients towards spinal anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a simple comparison between NB and GA for distal radius fixation has not been performed to date. Patients who preferred GA over regional anesthesia or those scheduled to undergo regional anesthesia expressed more fear of needle puncture [5] [6]. Rundgren et al and Galos et al suggested that patients undergoing distal radius fracture surgery under NB complained more frequently of delayed postoperative pain [3] [4].…”
Section: Introductionmentioning
confidence: 99%